The Role of Salivary miR-134-3p and miR-15b-5p as Potential Non-invasive Predictors for Not Developing Acute Mountain Sickness - Huang, He; Dong, Huaping; Zhang, Jianyang; Ke, Xianfeng; Li, Peng; Zhang, Erlong; Xu, Gang; Sun, Bingda; Gao, Yuqi (Frontiers in Physiology, 2019)
Background: Acute mountain sickness (AMS) is a crucial public health problem for high altitude travelers. Discriminating individuals who are not developing (AMS resistance, AMS-) from developing AMS (AMS susceptibility, AMS+) at baseline would be vital for disease prevention. Salivary microRNAs (miRNAs) have emerged as promising non-invasive biomarkers for various diseases. Thus, the aim of our study was to identify the potential roles of salivary miRNAs in identifying AMS- individuals pre-exposed to high altitude. Moreover, as hypoxia is the triggering factor for AMS, present study also explored the association between cerebral tissue oxygenation indices (TOI) and AMS development after exposed to high altitude, which was the complementary aim. Methods: In this study, 124 healthy men were recruited, and were exposed at simulated high altitude of 4,500 m. Salivary miR-134-3p and miR-15b-5p were measured at baseline (200 m). AMS was diagnosed based on Lake Louise Scoring System at 4,500 m. The measurements of physiological parameters were recorded at both the altitudes. Results: Salivary miR-134-3p and miR-15b-5p were significantly up-regulated in AMS- individuals as compared to the AMS+ (p < 0.05). In addition, the combination of these miRNAs generated a high power for discriminating the AMS- from AMS+ at baseline (AUC: 0.811, 95% CI: 0.731-0.876, p < 0.001). Moreover, the value of cerebral TOIs at 4,500 m were significantly higher in AMS- individuals, compared to AMS+ (p < 0.01). Conclusion: Our study reveals for the first time that salivary miR-134-3p and miR-15b-5p can be used as non-invasive biomarkers for predicting AMS- individuals pre-exposed to high altitude.